Effect of systematic physical exercise on the structural and functional changes in the ventricles of the heart - Богдановська [Nadezhda Bogdanovskaya], Надія Василівна (Slobozhanskyi Herald of Science and Sport, 2013)
We studied the effect of systematic physical activity, during the competition period , on the structural and functional parameters of the heart female athletes. It is shown that in the process of adaptation of the organism to systematic physical exercise a significant amount and intensity of the observed remodelingprocess.